Lateral hip and anterior groin pain - Division I women`s lacrosse - Patel, R. V.; Chu, J.; Stamatis, A. (International Journal of Exercise Science Conference Proceedings, 2025)
CASE HISTORY: A 22-year-old Division I female lacrosse athlete with prior left ACL reconstruction presented with progressive right lateral hip and anterior groin pain, intermittently radiating to the lateral thigh. She denied neurological symptoms, mechanical catching/locking, or instability, but reported occasional popping. Symptoms were minimally relieved by physical therapy, cupping, and dry needling. PHYSICAL EXAM: Initial: focal tenderness over the right lateral hip (TFL) and mild anterior hip-flexor tenderness; FABER/FADIR reproduced pain. Subsequent exams: full ROM, 5/5 strength, normal gait; FABER/FADIR negative; Trendelenburg, Ober, log roll, and heel strike negative. DIFFERENTIAL DIAGNOSES: Labral tear; FAI; gluteal tendinopathy (minimus/medius); greater trochanteric bursitis; femoral neck stress injury. TESTS & RESULTS: Radiographs unremarkable. MRI: insertional moderate gluteus minimus tendinosis with low-grade partial tear and mild peritendinitis; reactive greater trochanter marrow edema; reactive edema at right ischial tuberosity; mild gluteus medius and hamstring tendinosis. Labrum and articular cartilage intact. FINAL DIAGNOSIS: Right gluteus minimus tendinopathy with low-grade partial-thickness tear. DISCUSSION: Abductor tendinopathy is a frequent extra-articular cause of lateral hip pain and can mimic intra-articular disease. Prior contralateral ACL reconstruction likely altered lumbopelvic mechanics, increasing load on right abductors and predisposing to overuse. MRI distinguished abductor tendinopathy from labral pathology. PRP is reasonable after failed targeted rehab. OUTCOME OF THE CASE: Ultrasound-guided PRP to right abductor. Sleep pain improved; lateral tenderness decreased; spasms resolved. No sharp pain in rehab; residual tightness/fatigue and deep ache post-load. Follow-up ultrasound: less inflammation and smaller anechoic areas at minimus insertion. At six weeks, ~25% symptom improvement and functional gains. RETURN TO ACTIVITY AND FURTHER FOLLOW-UP: Phased rehab emphasized gluteal strength and lumbopelvic control. Light jogging began four weeks post-PRP, with gradual progression to running and sport-specific drills. Ongoing follow-up will guide adjunct therapy and determine the need for repeat imaging.